Factors Affecting Internet Banking Adoption: An Application of Adaptive LASSO - Jenkins, Hatice; Hesami, Siamand; Yesiltepe, Fulden (Tech Science Press, 2022)
This research investigates a broad range of possible factors affecting the adoption of new technology in the banking industry using adaptive LASSO and a standard logit model. The research integrated the adoption of the innovation framework and the technology acceptance theory to develop a conceptual framework for the analysis. Primary data was collected from 400 bank customers in North Cyprus. Risk perception and other customer-specific factors such as perceived risk index and negative attitude toward new technologies index were formulated for the proposed conceptual model. The findings indicated that individuals with a negative attitude toward new technology are least likely to adopt internet banking. In addition, the logit model suggested that age, education level, and general (innate) innovativeness significantly impact the adoption of internet banking. However, gender, income, occupation, perceived risk, familiarity with the internet, and social inclusion have no significant impact on internet banking adoption in North Cyprus.
Keywords: E-banking; business technology; internet banking adoption; adaptive LASSO method